2016
DOI: 10.1016/j.irfa.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Corporate debt maturity in the MENA region: Does institutional quality matter?

Abstract: We investigate corporate debt maturity structure in the MENA region and its firm and institutional determinants using a sample of 444 listed firms over the 2003-2011 period, or 3717 firm-year observations. We find a very limited use of long-term debt by MENA firms; long-term debt represents only 3.41% of the typical MENA firm's total debt, which is much less than what is reported in prior literature on other parts of the world. Consistent with the predictions of debt maturity theories and prior empirical findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
105
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(124 citation statements)
references
References 80 publications
16
105
0
3
Order By: Relevance
“…This study thus aims to bridge the gap in the literature and provides this evidence using a large sample of non-financial firms across MENA countries. More recently, Awartani (2015) reported that the better regulatory effectiveness, creditors' legal protection and enforcement of the rule of law are related to the usage of long-term debt by firms in the MENA region.…”
Section: The Importance Of Mena Contextmentioning
confidence: 99%
“…This study thus aims to bridge the gap in the literature and provides this evidence using a large sample of non-financial firms across MENA countries. More recently, Awartani (2015) reported that the better regulatory effectiveness, creditors' legal protection and enforcement of the rule of law are related to the usage of long-term debt by firms in the MENA region.…”
Section: The Importance Of Mena Contextmentioning
confidence: 99%
“…The MENA region is predominantly bank based, with limited development of equities and corporate bonds with some exception for the GCC countries. For firms in the MENA region, the level of long-term debt as a percentage of total debt is extremely low, reportedly to be around 3.41% (Awartani et al, 2016). This feature of the financial systems in the countries from the MENA region could be related to the nature of corporate borrowers in the region who often have higher level of opaqueness, and where controlling shareholders influence the disclosure of information.…”
Section: Literature Review and Empirical Hypotheses 21 Conventional mentioning
confidence: 99%
“…Based on data for the MENA region, Awartani et al [2016] found a positive influence of leverage, firm's size and assets tangibility on debt maturity structure. Contrary to the tenets of the signaling hypothesis, companies experiencing financial difficulties are found to be more reliant on short-term debt.…”
Section: Literature Reviewmentioning
confidence: 99%